CENTRAL SYSTOLIC BLOOD PRESSURE RELATES INVERSELY TO NITRIC OXIDE SYNTHESIS IN YOUNG BLACK ADULTS: THE AFRICAN-PREDICT STUDY. (April 2021) - Craig, Ashleigh; Mels, Catharina Mc; Tsikas, Dimitrios; Boeger, Rainer H.; Schwedhelm, Edzard; Schutte, Aletta E.; Kruger, Ruan
Abstract : Objective: Lower nitric oxide bioavailabilty associates with hypertension in diseased and elderly populations. With hypertension known to develop earlier in black populations, we compared both plasma and urinary nitric oxide-related markers and their associations with central systolic blood pressure and arterial stiffness in healthy young black and white adults. Design and method: We included healthy black and white men and women (n = 1110; 20–30 years) and measured central systolic blood pressure and pulse wave velocity, along with both plasma and urinary arginine, homoarginine, asymmetric dimethylarginine, symmetric dimethylarginine, as well as urinary ornithine/citrulline, nitrite and nitrate. Additionally, the urinary nitrate-to-nitrite ratio was calculated. Results: The black men and women had higher central systolic blood pressure and higher plasma arginine and asymmetric dimethylarginine, but lower urinary nitrate and urinary nitrate-to-nitrite ratio (all p< = 0.003) than their white counterparts. In single and forward stepwise multiple regression analyses, we found an inverse association of central systolic blood pressure (adj. R 2  = 0.124; β= –0.134; p = 0.006) and plasma homoarginine in black men. Central systolic blood pressure associated inversely with urinary nitrate-to-nitrite ratio in black women only (adj. R 2  = 0.171; β= –0.130; p = 0.029). In the white women, central systolic blood pressure associated positively with urinary asymmetric dimethylarginine (adj. R 2  = 0.372; β= 0.162; p = 0.015). Pulse wave velocity associated inversely with plasma asymmetric dimethylarginine (adj. R 2  = 0.253; β= –0.163; p = 0.024) in the white women only. Conclusions: The lower nitric oxide synthesis and the higher central systolic blood pressure in our black cohort support the notion of a potential increased risk for future large artery stiffness and hypertension development in later life. Figure. No caption available.